Composable Partial Multiparty Session Types - Stolze, Claude; Miculan, Marino; Di Gianantonio, Pietro (Formal Aspects of Component Software, 2021)
We introduce partial sessions and partial (multiparty) session types, in order to deal with open systems, i.e., systems with missing components. Partial sessions can be composed, and the type of the resulting system is derived from those of its components without knowing any suitable global type nor the types of missing parts. Incompatible types, due to e.g. miscommunications or deadlocks, are detected at the merging phase. We apply these types to a process calculus, for which we prove subject reduction and progress, so that well-typed systems never violate the prescribed constraints. Therefore, partial session types support the development of systems by incremental assembling of components.